DETERMINAN UNDERPRICING PADA PERUSAHAAN IPO DENGAN VARIABEL MODERASI DEWAN KOMISARIS (Studi Empiris pada Perusahaan yang Melakukan IPO di BEI Tahun 2017-2019) - Fadhilah Dwi Lailita Safitri; Marsono Marsono (Diponegoro Journal of Accounting, 2022)
The aim of this study is to examine the effect of profitability, auditor reputation, underwriter reputation, and size firm on the underpricing of IPO shares companies that moderated by board of commissioners. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX). The population in this study consists of all IPO firm in Indonesia Stock Exchange on the period 2017 – 2019. Sample determined with purposive sampling method. Total sample of this research is 109 companies. This study used Structural Equation Model – Partial Least Square (SEM-PLS) by SmartPLS 3.0 software. The result of this study show that profitability, auditor reputation, underwriter reputation, and firm size had no significant effect on the level of underpricing IPOs. Different with variable board of commissiners that had significant effect on the level of underpricing IPOs but the board of commissioners can be moderated the effect of profitability, auditor reputation, underwriter reputation, and firm size to the level of underpricing.